Clinical spectrum, genetic complexity and therapeutic approaches for retinal disease caused by ABCA4 mutations. (November 2020) - Cremers, Frans P.M.; Lee, Winston; Collin, Rob W.J.; Allikmets, Rando
Abstract: The ABCA4 protein (then called a "rim protein") was first identified in 1978 in the rims and incisures of rod photoreceptors. The corresponding gene, ABCA4, was cloned in 1997, and variants were identified as the cause of autosomal recessive Stargardt disease (STGD1). Over the next two decades, variation in ABCA4 has been attributed to phenotypes other than the classically defined STGD1 or fundus flavimaculatus, ranging from early onset and fast progressing cone-rod dystrophy and retinitis pigmentosa-like phenotypes to very late onset cases of mostly mild disease sometimes resembling, and confused with, age-related macular degeneration. Similarly, analysis of the ABCA4 locus uncovered a trove of genetic information, including >1200 disease-causing mutations of varying severity, and of all types – missense, nonsense, small deletions/insertions, and splicing affecting variants, of which many are located deep-intronic. Altogether, this has greatly expanded our understanding of complexity not only of the diseases caused by ABCA4 mutations, but of all Mendelian diseases in general. This review provides an in depth assessment of the cumulative knowledge of ABCA4 -associated retinopathy – clinical manifestations, genetic complexity, pathophysiology as well as current and proposed therapeutic approaches.